Risk factors for left ventricular dysfunction in adulthood: role of low birth weight - Huynh Quan L.; Venn Alison J.; Magnussen Costan G.; Yang Hong; Dwyer Terence; Marwick Thomas H. (WILEY PERIODICALS, INC, 2022)
Aims This study aimed to determine the relationship of low birth weight (LBW) with adult cardiac structure and function and investigate potential causal pathways.
Methods and results A population-based sample of 925 Australians (41.3% male) were followed from childhood (aged 7-15 years) to young adulthood (aged 26-36 years) and mid-adulthood (aged 36-50 years). Left ventricular (LV) global longitudinal strain (GLS, %), LV mass index (LVMi, g/m(2.7)), LV filling pressure (E/e'), and left atrial volume index (g/m(2)) were measured by transthoracic echocardiography in mid-adulthood. Birth weight category was self-reported in young adulthood and classified as low (<= 5 lb or <= 2270 g), normal (5-8 lb or 2271-3630 g), and high (>8 lb or >3630 g). Of the 925 participants, 7.5% (n = 69) were classified as LBW. Compared with participants with normal birth weight, those with LBW had 2.01-fold (95% confidence interval: 1.19, 3.41, P = 0.009) higher risks of impaired GLS (GLS > -18%) and 2.63-fold (95% confidence interval: 0.89, 7.81, P = 0.08) higher risks of LV hypertrophy (LVMi > 48 g/m(2.7) in men or >44 g/m(2.7) in women) in adulthood, independent of age, sex, and any socio-economic factors. Participants with LBW significantly increased body fat from childhood to adulthood relative to their peers and had greater levels of triglycerides, fasting glucose, and arterial stiffness in adulthood. These risk factors were the strongest mediators and explained 54% of the LBW effect size on adult GLS and 33% of the LBW effect size on LVMi. The remaining of these associations was independent of any of the measured risk factors.
Conclusions Low birth weight was associated with impaired cardiac structure and function in mid-adulthood. This association was only partially explained by known risk factors.